2020
DOI: 10.3390/ijms21207753
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Supplementation in the Treatment of Neurotoxicity Induced by Platinum-Based Chemotherapeutics—A Review

Abstract: Cancer represents one of the most pernicious public health problems with a high mortality rate among patients worldwide. Chemotherapy is one of the major therapeutic approaches for the treatment of various malignancies. Platinum-based drugs (cisplatin, oxaliplatin, carboplatin, etc.) are highly effective chemotherapeutic drugs used for the treatment of several types of malignancies, but their application and dosage are limited by their toxic effects on various systems, including neurotoxicity. Simultaneously, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 158 publications
(196 reference statements)
2
56
0
1
Order By: Relevance
“…At lower platinum compound and higher concentrations of PARP and PI3K a synergistic effect likely appear and a regression-based model could indicate an overall synergy that may explain the conflict between our results ( Figure 1 ) and the findings of others [ 27 , 28 , 29 , 32 ]. Additionally, platinum compounds induce ROS production [ 33 ] and PARP inhibitors are known to protect against oxidative stress [ 23 ], what could contribute to the absence of synergy between the PARP inhibitor and the platinum agent that we observed. Accordingly, blocking the PI3K/Akt pathway by the PI3K inhibitor LY294002 increased the cytotoxicity of olaparib and oxaliplatin co-treatment, although the effect did not reach a statistically significant level ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At lower platinum compound and higher concentrations of PARP and PI3K a synergistic effect likely appear and a regression-based model could indicate an overall synergy that may explain the conflict between our results ( Figure 1 ) and the findings of others [ 27 , 28 , 29 , 32 ]. Additionally, platinum compounds induce ROS production [ 33 ] and PARP inhibitors are known to protect against oxidative stress [ 23 ], what could contribute to the absence of synergy between the PARP inhibitor and the platinum agent that we observed. Accordingly, blocking the PI3K/Akt pathway by the PI3K inhibitor LY294002 increased the cytotoxicity of olaparib and oxaliplatin co-treatment, although the effect did not reach a statistically significant level ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we studied ROS production which reflects metabolic plasticity [ 38 ] and is compatible with cell culturing conditions. Increased ROS production by the platinum compounds [ 33 ] could induce DNA breaks that may accumulate when PARP is inhibited leading to cell death. Such a mechanism could account for the observed synergism between platinum compounds and PARP inhibitors [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, advancement in medical science have produced several anticancer agents including chemotherapy drugs that have increased the life expectancy of many cancer patients (Schirrmacher 2019;Zajączkowska et al 2019). Chemotherapeutic drugs plays significant roles in mitigating the progression of cancer, however, the cytotoxic effects of these drugs are not only restricted to the target tissues, but also significantly affects several other organs in the patients resulting in varying degrees of side effects and toxicities (Stankovic et al 2020;Argyriou et al 2012;Trendowski et al 2019;Hakiminia et al 2019;Zajączkowska et al 2019). CISP, a widely used platinum based anticancer and antitumor agent has been widely documented to adversely affect the nervous system leading to peripheral neuropathy characterised by motor, sensory and autonomic dysfunction (Park et al 2013;McWhinney et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a prolonged and high oxaliplatin intracellular accumulation, induced ROS overproduction mediated by mitochondrial impairment (Massicot et al, 2013). Thus, even if specific transporter polymorphisms are not beneficial for patients that unfortunately do not correctly excrete oxaliplatin leading to its accumulation, the simultaneous use of antioxidant molecules during a chemotherapy regimen could help to retrieve and ameliorate the oxaliplatin-induced neuropathic pain (De Monaco et al, 2014;Stankovic et al, 2020).…”
Section: Genetic and Epigenetic Role In Oxaliplatin-induced Neuropathic Painmentioning
confidence: 99%